Grains market in the countries in the Black Sea, Caspian Sea basins and in countries with indirect access to the Black Sea through the Danube: Recent developments - Cecilia Alexandri; Sorinel Ionel Bucur (Agrarian Economy and Rural Development - Trends and Challenges. International Symposium. 13th Edition, 2022)
The current context generated by the armed conflict between Ukraine and Russia brings to the foreground an important issue concerning the international trade in cereals, mainly the transit of cereals from/to Ukraine via the Black Sea to/from Ukraine's trading partners. While the transit of cereals from/to Ukraine is mainly via the Black Sea, the cereal trade from Russia can be done both through the Black Sea and the Caspian Sea, given Russia's position with direct access to the two seas. In this context, the present study aims to carry out an analysis of the evolution of the cereal market in the countries bordering the Black Sea and the Caspian Sea, as well as in some countries with indirect access to the Black Sea, through the Danube, the analysis focusing on the main cereals, namely wheat and maize.
Keywords: Q10; Q11; Q17; 330; pia÷ta cerealelor; produc÷tie; cerere; comer÷t exterior